2017
DOI: 10.1515/eje-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Biologically informed ecological niche models for an example pelagic, highly mobile species

Abstract: Background: Although pelagic seabirds are broadly recognised as indicators of the health of marine systems, numerous gaps exist in knowledge of their at-sea distributions at the species level. These gaps have profound negative impacts on the robustness of marine conservation policies. Correlative modelling techniques have provided some information, but few studies have explored model development for non-breeding pelagic seabirds.Here, I present a first phase in developing robust niche models for highly mobile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Temporally explicit approaches to correlative niche modelling methods have been at the core of movement ecology analyses for some time (Gschweng et al., 2012), and yet the distributional ecology community has yet to adopt a similar approach. Indeed, despite long‐standing understanding that traditional (time‐averaged) correlative modelling approaches lead to over‐generalization of climatic niches (Barve et al., 2014; Ingenloff, 2017; Peterson et al., 2005), efforts to incorporate time‐specificity into the modelling framework have a fairly punctuated history. Seasonal modelling has been the gold star method for some time (Laube et al., 2015; Skov et al., 2016; Soriano‐Redondo et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporally explicit approaches to correlative niche modelling methods have been at the core of movement ecology analyses for some time (Gschweng et al., 2012), and yet the distributional ecology community has yet to adopt a similar approach. Indeed, despite long‐standing understanding that traditional (time‐averaged) correlative modelling approaches lead to over‐generalization of climatic niches (Barve et al., 2014; Ingenloff, 2017; Peterson et al., 2005), efforts to incorporate time‐specificity into the modelling framework have a fairly punctuated history. Seasonal modelling has been the gold star method for some time (Laube et al., 2015; Skov et al., 2016; Soriano‐Redondo et al .…”
Section: Discussionmentioning
confidence: 99%
“…The result is a single, static view of predicted suitability for the study species, which has been the topic of discussion in light of species that switch among multiple niches between seasons (Martínez‐Meyer et al., 2004). These approaches can result in over‐generalization of estimates of ecological niches (Barve et al., 2014; Ingenloff, 2017; Peterson et al., 2005), particularly for migratory or behaviourally complex organisms (Ingenloff, 2017; Peterson et al., 2005). Modelling mobile species presents a particularly challenging situation because, to be meaningful, predictive models must capture both a seasonally dynamic landscape and associated species movements, which traditional methods are unable to account for (Elith et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, six climate variables were selected: annual mean temperature, mean daytime temperature range, isothermality, seasonality in temperature, annual precipitation, seasonality in precipitation. The oceanographic variables used were sea surface temperature (SST) and marine net primary productivity (mg C m −2 day −1 ), as they are considered the main descriptors of the spatial distribution of seabirds (Quillfeldt et al, 2015; Ingenloff, 2017). These variables were obtained from the National Oceanic and Atmospheric Administration (NOAA, http://www.ngdc.noaa.gov/).…”
Section: Methodsmentioning
confidence: 99%
“…ENM is often applied within a time-averaged framework in which the values of environmental variables are averaged over time spans that are not in temporal registration with the occurrence records upon which models are calibrated or tested [55,57]. While useful for exploring species distributions at a broad level, modeling within a time-averaged framework can elide complex effects of the environment on an organism, especially highly mobile or behaviorally complex species [55,[58][59][60][61]. Of particular concern to conservation work, studies have shown that temporal mismatches in the time period spanned by occurrence data and the climate baseline can decrease the utility and accuracy of ENM products [62][63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%